Mark Dion - Misadventures of a 21st-century naturalist - Barrett, Andrea 1954-; Basta, Sarina; Bradnock, Lucy; Corrin, Lisa G.; Duffy, Kathrinne; Markonish, Denise; Nisbet, James 1981-; Sheehy, Colleen J. 1953-; Suzuki, Sarah (The Institute of Contemporary Art, 2017)
A comprehensive survey of American artist Mark Dion, examining three decades of his critically engaged practice interrogating our relationship with nature The first book in two decades to consider the entire oeuvre of Mark Dion (b. 1961), this volume examines thirty years of the American artist's pioneering inquiries into how we collect, interpret, and display nature. Part of a generation of artists expanding institutional critique in the 1990s, Dion adopted the methods of the archaeologist or the natural history museum, juxtaposing natural objects, taxidermy, books, and more to reorganize the natural and the manmade in poetic, witty ways. These sculptures, installations, and interventions offer novel approaches to questioning institutional power, which he sees as connected to the control and representation of nature. Generously illustrated, this publication introduces new insights and features more than seventy-five artworks
On the occasion of the exhibition ... The Institute of Contemporary Art, Boston, October 4, 2017 - January 1, 2018
Keywords: Dion, Mark -- 1961-; Natur -- Motiv; Kunst; Dion, Mark / 1961- / Exhibitions; Installations (Art) / Exhibitions; Nature (Aesthetics) / Exhibitions; Ausstellungskatalog; Ausstellungskatalog -- Institute of Contemporary Art -- 04.10.2017-01.01.2018 -- Boston, Mass.; Bildband